Functional Studies of microRNAs in Neural Stem Cells: Problems and Perspectives - Åkerblom, Malin; Sachdeva, Rohit; Jakobsson, Johan (Frontiers in Neuroscience, 2012)
In adult mammals, neural stem cells (NSCs) are found in two niches of the brain; the subventricular zone by the lateral ventricles and the subgranular zone of the dentate gyrus in the hippocampus. Neurogenesis is a complex process that is tightly controlled on a molecular level. Recently, microRNAs (miRNAs) have been implicated to play a central role in the regulation of NCSs. miRNAs are small, endogenously expressed RNAs that regulate gene expression at the post-transcriptional level. However, functional studies of miRNAs are complicated due to current technical limitations. In this review we describe recent findings about miRNAs in NSCs looking closely at miR-124, miR-9, and let-7. In addition, we highlight technical strategies used to investigate miRNA function, accentuating limitations, and potentials.